DESIGN ANALYSIS OF CURRICULUM DEVELOPMENT OF PUBLIC SECTOR ACCOUNTING STUDY PROGRAM BASED ON INDEPENDENT CAMPUS LEARNING ON INDEPENDENT CAMPUS KUPANG STATE POLYTECHNIC - Hapsa Usman; Deetje Manuain; Nonce Farida Tuati (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2022)
Independent Campus is a program that has been launched by the government through the Ministry of Education and Culture, Research and Technology. There are four main points regarding the design of the Merdeka Campus: first, regarding the freedom to open new study programs for A and B accredited universities; second, re- accreditation is automatic for all ratings and can be proposed at any time; third, the freedom to form State Universities as Legal Entities from State Universities as Public Service Agencies and State Universities as Work Units; fourth, the rights given to students to engage in activities outside the study program and the change in the definition of credit from